PENYULUHAN TENTANG PEMANFAATAN INFORMASI BERBASIS DIGITAL DI DESA BAROS KECAMATAN BAROS KABUPATEN SERANG - Siti Maryam; Aniqotul Ummah; Danis Tri Saputra Wahidin; Mansur Juned (AMMA : Jurnal Pengabdian Masyarakat, 2022)
A number of development sectors in society have become unstable and disrupted due to covid-19. The most disrupted sector due to covid-19 is the economic sector. This is due to the lock down policy provided by the government to limit and close access to community mobilisation both internationally and nationally. So then, the government and society must have other creativity in finding solutions so that mobilisation is not disrupted. Following up on this, the research team together with Baros village representatives conducted counselling related to the utilisation of digital-based information. We believe that through the use of internet technology to utilise access to information, it is hoped that Indonesia, especially the Baros village environment, will recover from the economic downturn caused by Covid-19.